2012
DOI: 10.4082/kjfm.2012.33.5.311
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Occupational Stress and Gastric Disease in Male Workers

Abstract: BackgroundPhysical and mental health of workers is threatened due to various events and chronic occupational stress. This study was conducted to investigate the relationship between occupational stress and gastric disease in male workers of the shipbuilding industry.MethodsOccupational stress measured among a total of 498 workers of a shipbuilding firm who visited the hospital for health examination using the Korean Occupational Stress Scale (KOSS)-short form, and the relationship between sociodemographic fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…Our research showed an important relation between the job satisfaction and the self-perceived state of health what corresponds to other researches [2,8,9]. System of rewards (formal and informal appreciation) is closely related to the job satisfaction [23,24]. Our result show that aspects which are pillars of the reward system SHS Web of Conferences 92, 0 (recognition for work, salary adequacy, opportunity to develop) affect significantly the selfperceived state of health.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our research showed an important relation between the job satisfaction and the self-perceived state of health what corresponds to other researches [2,8,9]. System of rewards (formal and informal appreciation) is closely related to the job satisfaction [23,24]. Our result show that aspects which are pillars of the reward system SHS Web of Conferences 92, 0 (recognition for work, salary adequacy, opportunity to develop) affect significantly the selfperceived state of health.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, there are two methodological notes to make: (1) If the research concerns the workers/employees who have already gastric/duodenal, there is a significant relation with the adverse working conditions [14]. On the other hand, if the subjects of research are workers/employees who face adverse/stressful working conditions, the relation with the peptic ulcer might not be always significant [23]; evidently due to a more complex disease etiology and possible specificity of the sample. This knowledge might apply analogically to other variables and research designs.…”
Section: Discussionmentioning
confidence: 99%
“…Another study examined the relationship between job stress and gastric disease among shipbuilding male workers. It was reported that the risk of gastric disease was significantly higher in the high job stress group than in the low job stress group in the occupational climate subcategory (OR 2.82, 95% CI 1.15–6.91) [ 33 ]. In a study on the effects of psychosocial factors of IBS among firefighters, the risk of IBS was higher in the following KOSS subcategories: job demand (OR 1.79, 95% CI 1.11–2.89), interpersonal conflict (OR 2.21, 95% CI 1.25–4.33), and lack of reward (OR 2.39, 95% CI 1.08–5.26) [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estes distúrbios possuem alta prevalência específica por idade, independente do tipo de agravo gástrico, e que tende a aumentar com a idade (SIPPONEN et al, 2015). Ainda para caracterizar a influência da idade na ocorrência de agravos gastrointestinais, Lihm et al (2012), ao compararem a ocorrência de doença gástrica às características sociodemográficas de um grupo de trabalhadores, identificaram que os sujeitos com maior idade, assim como com escolaridade de ensino médio e com cônjuge, eram provavelmente portadores ou mais suscetíveis a doença gástrica.…”
Section: Discussionunclassified